Simplified Template Cross Section measurements of associated V H production in the H → b¯b decay channel with √ s = 13 TeV proton-proton collisions at the ATLAS experiment - Atkin, Ryan (Department of Physics, 2025)
This thesis presents a Simplified Template Cross-Section (STXS) measurement of the production of the SM Higgs boson in association with a W or Z boson, where the Higgs boson decays to b ¯b and the W/Z boson (V ) decays leptonically. The data used is the full Run-2 ATLAS dataset, corresponding to 140 fb−1 of integrated luminosity, which was collected in proton-proton collisions at a centre of mass energy of √ s = 13 TeV. This process was previously observed by both the ATLAS collaboration in 2021, and the CMS collaboration in 2023, measuring the signal strength to be µ bb V H = 1.02+0.18 −0.17 and µ bb V H = 1.15+0.22 −0.20 respectively. The measurement in this thesis expands the STXS regions to 10 by splitting each region by the number of jets additional to the Higgs decay products. Some of these regions have not been studied yet and so this measurement acts a feasibility study for those regions. All 10 of the STXS regions studied have a signal strength which agrees well with the standard model expectation. While some signal strengths are negative, their uncertainties were large enough to still agree with a value of 1. Increasing the minimum requirement on the transverse momentum of the additional jets was found to decrease the uncertainties on the signal strengths for the regions with at least one additional jet. However, this reduction was not enough to obtain statistically significant results in some of the additional jets STXS regions.